Leadership, organizational culture, and quality of human resources towards job satisfaction and performance - Fachri, Muhammad; Paminto, Ardi; Effendi, Aji Sofyan (Technium Social Sciences Journal, 2021)
Human resources (HR) is always interesting to investigate and how they are progressing so that they can set goals in the workplace. This study aims to determine the influence of leadership style, organizational culture, and quality of HR on job satisfaction and employee performance in the Regional Financial and Asset Management Agency of East Kalimantan Province (Indonesia). Explanatory and descriptive-based study design. To determine the extent of the relationship based on the proposed hypothesis, data were collected using survey techniques for all 103 employees. Data analysis was processed and interpreted through Structural Equation Modeling-Partial Least Square (SEM-PLS). Interestingly, we found that leadership style and organizational culture did not have a significant effect on job satisfaction. On the one hand, the quality of HR has a significant effect on job satisfaction. In the second experiment, leadership style, organizational culture, quality of HR, and job satisfaction have had a significant impact on employee performance. This study is expected to become a new reference for future studies by considering the sample size, analysis tools, and variables that can be developed again.